Analysis of the Viscosity Value of Packaged Oil with Bulk Oil Using Tracker Video Analysis - Budiman, Budiman; Prima, Eka Cahya; Riandi, Riandi; Suwarma, Irma Rahma (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
The utilization of STEM-based technology is essential for activating students in learning. One of the media that can be used in STEM-based learning is the Analysis Video Tracker. Analysis Video Tracker is an application used to analyze speed, velocity, acceleration, force, gravitational field, conversion, and energy conservation. This study used the Video Tracker Analysis application, which aims to observe the effect of object mass in measuring viscosity. Second, to assess the viscosity values between bulk oil and packaged oil. Finally, to examine the reliability of data generated by video tracker analysis application. The research method used in this study is an experimental method of analyzing video recordings of the motion of falling objects into a liquid with Tracker Software version 6.1.0. This research data was analyzed through the Analysis Video Tracker application, excel, and SPSS version 25. The results of the research in this article. First, the mass of the object used to measure affects viscosity time (s), distance traveled (cm), speed (cm/s), and acceleration (cm/s2). Secondly, the viscosity value of bulk oil is higher (3.978 Nm/s2) than packaged oil (3.124 Nm/s2). Third, the data obtained from the video tracker analysis application is reliable or consistent. The results of this research are expected to serve as a reference and alternative in using learning media, especially on the topic of viscosity, and to become a reference in selecting oils for food processing.